Peran Kuliah Kerja Nyata sebagai Wujud Pengabdian kepada Masyarakat di Universitas Islam Internasional Darullughah Wadda’wah Pasuruan - Juharoh, Juharoh (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Community Service Program (KKN) is an implementation of the Tri Dharma of Higher Education, encompassing community service, teaching, and research. This study was conducted at Darullughah Wadda’wah Islamic Boarding School in Pasuruan, during the post-Covid-19 pandemic, focusing on the flagship program "Estafet Mufrodat." This program aimed to enhance the Arabic language skills of female students (santriwati), who are required to speak Arabic in their daily lives at the boarding school. The 2023 KKN was conducted entirely within the boarding school complex, emphasizing the empowerment of santriwati through language activities. The research methodology included problem identification through interviews, program planning in collaboration with the boarding school management, implementation, evaluation, and program sustainability. The results indicate that the Estafet Mufrodat program successfully improved the Arabic language proficiency of santriwati, created an enjoyable learning environment, and supported the implementation of the Tri Dharma of Higher Education. In conclusion, despite challenges due to the pandemic, KKN remained effective as a means of community service and the development of students' abilities in the context of community empowerment.